2012
DOI: 10.1021/bi3003378
|View full text |Cite
|
Sign up to set email alerts
|

Toward Understanding the Mechanism of Ion Transport Activity of Neuronal Uncoupling Proteins UCP2, UCP4, and UCP5

Abstract: Neuronal uncoupling proteins (UCP2, UCP4, and UCP5) have crucial roles in the function and protection of the central nervous system (CNS). Extensive biochemical studies of UCP2 have provided ample evidence of its participation in proton and anion transport. To date, functional studies of UCP4 and UCP5 are scarce. In this study, we show for the first time that, despite a low level of amino acid sequence identity with the previously characterized UCPs (UCP1-UCP3), UCP4 and UCP5 share their functional properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
101
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(111 citation statements)
references
References 54 publications
(201 reference statements)
10
101
0
Order By: Relevance
“…Given its localization in the IMM, interaction of CL with UCP1 and its influence on this protein structure and function would not be surprising. In a previous study we reported that the proton transport rates of UCP2 and UCP5 in lipid vesicles were increased in the presence of CL (17).…”
Section: Located In the Inner Mitochondrial Membrane (Imm)mentioning
confidence: 86%
See 2 more Smart Citations
“…Given its localization in the IMM, interaction of CL with UCP1 and its influence on this protein structure and function would not be surprising. In a previous study we reported that the proton transport rates of UCP2 and UCP5 in lipid vesicles were increased in the presence of CL (17).…”
Section: Located In the Inner Mitochondrial Membrane (Imm)mentioning
confidence: 86%
“…Recombinant protein expression in bacterial systems is an efficient and inexpensive method for protein production. However, refolding of UCP1 from inclusion bodies could only yield partially folded proteins in mild detergents and liposomes (6,17,19). The recent new development of bacterial strains, fusion proteins, and alternative expression methods provide other possibilities for recombinant UCP1 to be targeted toward the inner membrane of Escherichia coli (20 -22).…”
Section: Located In the Inner Mitochondrial Membrane (Imm)mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the widely discussed functions for UCP4-another member of the same subfamily that is localized in neurons and neurosensory cells (6)(7)(8)(9)-is the regulation of ROS by decreasing the pmf (10,11). Although there is no unambiguous evidence revealing the exact UCP4 function, it was shown that UCP4 transports protons similar to UCP1 (12). It is, therefore, assumed that UCP4 and other UCPs possibly compete for protons with other proton-consuming proteins, including ATP synthase, but this phenomenon has not yet been studied in detail (13).…”
mentioning
confidence: 99%
“…UCP2 and UCP3 are activated by superoxide from the mitochondrial inner membrane, and can reduce ROS generation (21). UCP4 and UCP5 are specifically localized to the brain, and associated with reducing the mitochondrial membrane potential (22).…”
Section: Introductionmentioning
confidence: 99%